Peningkatan Penguasaan Konsep Matematika terhadap Siswa SDN 2 Kembiritan Melalui Media Pembelajaran Matematika - Robisha Zarifa Ribaah; Alex Haris Fauzi; Mila Rohmatun Nisa; Marsida Aulia Rahma; Muhamad Putra Rus Affandi (Jurnal Kemitraan Masyarakat, 2024)
The research was conducted by providing training and enhancing the understanding of mathematical concepts among the fifth-grade students of SDN 2 Kembiritan. The goal is to improve the students' understanding of mathematical concepts. The methods used in this activity are direct practical methods and lecture methods. The instruments used were pre-tests and post-tests. Based on the service, it can be concluded that the use of the Fractional Clock media has proven to be able to improve the learning outcomes of fifth-grade students at SDN 2 Kembiritan, as evidenced by the learning outcomes after the use of the learning media meeting the established criteria, with 70% of students achieving scores above the Minimum Completeness Criteria (KKM).